2007
DOI: 10.1016/j.crme.2007.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann method for melting/solidification problems

Abstract: The present work uses the Lattice Boltzmann method for solving solid/liquid phase change problems. The computed results demonstrate a good agreement with the existing benchmark solution for natural convection and with the experimental solution for solid/liquid interface interacting with the flow field. To cite this article: E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Despite many achievements to date, some controversial issues have to be further resolved for improved understanding of the bluff-body flow. It was used for simulating the flow field in wide ranges of the engineering applications such as heat transfer problems [17,18], phase change problems [19][20][21], cylindrical structure [22,23], turbulent flow [24,25], porous media [26], multiphase flow [27], microchannel [28], etc. The numerical studies carried out by Jordan et al indicated that the front stagnation point shifted to the high velocity side in the shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many achievements to date, some controversial issues have to be further resolved for improved understanding of the bluff-body flow. It was used for simulating the flow field in wide ranges of the engineering applications such as heat transfer problems [17,18], phase change problems [19][20][21], cylindrical structure [22,23], turbulent flow [24,25], porous media [26], multiphase flow [27], microchannel [28], etc. The numerical studies carried out by Jordan et al indicated that the front stagnation point shifted to the high velocity side in the shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal Lattice Boltzmann method for coupled heat and incompressible fluid flow fields has been used previously to simulate convection problems [29,[82][83][84] and been coupled to cellular automata (CA) to simulate the solidliquid phase change for pure materials. [7,31,32,36,79] If it is assumed that the fluid is incompressible, viscous heat dissipation is negligible, and no work is done by the external pressure, an additional set of distribution functions can be introduced to the model for heat transport. These are analogous to those for solute (the heat is advected as a passive scalar), but include a heat diffusivity, internal energy density, and a heat source term in place of solute diffusivity, concentration, and the solute source term, respectively.…”
Section: B the Lattice Boltzmann Methodsmentioning
confidence: 99%
“…Additionally, Morville et al [28] used COM-SOL Multiphysics ® to simulate the fluid flow, melting, and transient temperature conditions encountered during direct laser metal deposition. Another approach has been based on the use of the Lattice Boltzmann method (LB), which is an attractive method for solving this particular fluid transport problem (relative to NavierStokes algorithms) because of its ease of handling complex geometries, [29,30] ease of modeling the changing boundary conditions found in solidification [31,32] and its ability to model coupled fluid, heat, and solute transport problems. [7,31,33] Additionally, the method is computationally efficient and easily parallelized.…”
Section: The Laser Engineered Net Shaping (Lens™)mentioning
confidence: 99%
“…In recent years, methods based on lattice Boltzmann equation (LBE) has recently become an alternative for simulating fluid flows in channels [19], curved boundaries [20-23], nanofluids [24,25], and phase-change [26][27][28][29][30][31]. Unlike conventional computational fluid dynamics (CFD) methods based on the discretization of macroscopic continuum equations, the LBE method is based on microscopic models and mesoscopic kinetic equations in which the combined behavior of the particles is applied to simulate the physical mechanism of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…Chatterjee and Chakraborty [38] also developed a hybrid lattice Boltzmann model (LB) model for handling conduction solidification in a single-component configuration. Semma et al [27] used LBM to solve Rayleigh-Benard (RB) problem with phase change. Semma et al [27] used LBM to solve Rayleigh-Benard (RB) problem with phase change.…”
Section: Introductionmentioning
confidence: 99%